Unveiling the economic burden of diseases in aquatic animal food production in India - Patil, P. K.; Geetha, R.; Mishra, S. S.; Abraham, Thangapalam Jawahar; Solanki, H. G.; Krupesha Sharma, S. R.; Pradhan, P. K.; Manna, S. K.; Avunje, S.; Abhinaya, D.; Felix, K. Thomas; Vinay, T. N.; et al. (Frontiers in Sustainable Food Systems, 2025)
Economic burden of diseases on Indian aquaculture sector was estimated to be US$ 2.48 B, 14.95% of annual aquaculture production value. Analysis revealed a higher cost of disease (US$ t−1) in shrimp (1,224.82) followed by marine fish (815.87), IMC+ (364.89), tilapia (260.34), IMC (200.70), and pangasius (pond 198.92; cage 168.36). The major contributors to the disease burden included production loss (23.90%), expenses on prophylactics (50.31%) and therapeutics (17.26%). The economic loss was dominated by diseases of multiple etiology (US$ 468.27 M), bacterial hemorrhagic septicemia (US$ 326.47 M), and epizootic ulcerative syndrome (US$ 88.12 M) in finfish and by Enterocytozoon hepatopenaei infection (US$ 571.24 M) in shrimp. Multinomial logit regression identified farm size, water source and exchange, stocking biomass and feed type as the main determinants of disease. The study findings would assist in prioritizing resource allocation and developing intervention strategies at the national level for effective and targeted disease management.